Regulation of citrate synthase activity in methylotrophs by reduced nicotinamide-adenine dinucleotide, adenine nucleotides and 2-oxoglutarate. - Colby, J (1975)
Citrate synthase from two typical facultative methylotrophs, but not from four obligate methylotrophs or from two restricted facultative methylotrophs, is inhibited by 0.1 mM-NADH. ATP or ADP (both at 10mM) inhibits all the citrate synthases, whereas 2-oxoglutarate (10mM) inhibits those from only three of the eight methylotrophs.